The conserved histone chaperone LIN‐53 is required for normal lifespan and maintenance of muscle integrity in Caenorhabditis elegans. Issue 6 (9th August 2019) - Müthel, Stefanie; Uyar, Bora; He, Mei; Krause, Anne; Vitrinel, Burcu; Bulut, Selman; Vasiljevic, Djordje; Marchal, Iris; Kempa, Stefan; Akalin, Altuna; Tursun, Baris
Abstract: Whether extension of lifespan provides an extended time without health deteriorations is an important issue for human aging. However, to which degree lifespan and aspects of healthspan regulation might be linked is not well understood. Chromatin factors could be involved in linking both aging aspects, as epigenetic mechanisms bridge regulation of different biological processes. The epigenetic factor LIN‐53 (RBBP4/7) associates with different chromatin‐regulating complexes to safeguard cell identities in Caenorhabditis elegans as well as mammals, and has a role in preventing memory loss and premature aging in humans. We show that LIN‐53 interacts with the nucleosome remodeling and deacetylase (NuRD) complex in C. elegans muscles to ensure functional muscles during postembryonic development and in adults. While mutants for other NuRD members show a normal lifespan, animals lacking LIN‐53 die early because LIN‐53 depletion affects also the histone deacetylase complex Sin3, which is required for a normal lifespan. To determine why lin‐53 and sin‐3 mutants die early, we performed transcriptome and metabolomic analysis revealing that levels of the disaccharide trehalose are significantly decreased in both mutants. As trehalose is required for normal lifespan in C. elegans, lin‐53 and sin‐3 mutants could be rescued by either feeding with trehalose or increasing trehalose levels via the insulin/IGF1 signaling pathway. Overall, our findings suggest that LIN‐53 is required for maintaining lifespan and muscle integrity through discrete chromatin regulatory mechanisms. Since both LIN‐53 and its mammalian homologs safeguard cell identities, it is conceivable that its implication in lifespan regulation is also evolutionarily conserved. Abstract : The histone chaperone LIN‐53 links lifespan and healthspan regulation. Through the NuRD chromatin‐remodeling complex, LIN‐53 maintains muscle integrity while lifespan is controlled through the chromatin‐silencing complex SIN3.